THE EFFECT OF IMMERSION IN 50% CONCENTRATION OF KASTURI LEAF EXTRACT (MANGIFERA CASTURI) ON THE DISCOLORATION OF HEAT CURED ACRYLIC RESIN - Agung Satria Wardhana; Mikael Manggala Silaen; Rahmad Arifin (FKG Unlam, 2023)
ABSTRACTBackground: Heat cured acrylic resin and alkaline proxide are the most used material for denture base and denture cleaner. However, the cost of denture cleanser and its discoloration effect after long term use became the major disadvantages of this material. Kasturi leaf extract, in 50% concentration, had been proven to have antibacterial and antifungal effect, such as a denture cleanser properties.. Objective: This study was to determine the discoloration effect of immersing heat cured resin acrylic in to 50% Kasturi leaf extract solution compared to alkaline peroxide and distilled water. Material and Methods: This study used 24 samples of heat cured acrylic following ADA specification no 17, with 15 milimeters diameter and 2 millimeters of thickness. The 50% Kasturi leaf extract treatment group and the control group alkaline peroxide and aquades. Each group consisted of 8 samples which measured the discoloration before and after being immersed for 5 days. The discoloration of the sample was tested using a series of digital analysis tools. The results obtained then converted into the equation of ΔE= [(ΔL)2 + (Δa)2 + (Δb)2]1/2. Results: One Way ANOVA and Post Hoct Bonferroni statistical tests showed that there was a significant difference (p <0.05) between the immersion groups in 50% Kasturi leaf extract (6.75 ± 1.31), alkaline peroxide (3.29 ± 0, 57) and distilled water (2.04 ± 0.60). Conclusion: A 50% solution of Kasturi leaf extract has an effect on the discoloration of heat cured type acrylic resin. Keywords: Discoloration, Heat cured acrylic resin, Kasturi leaves